Language skills at corrected age 2;0 are poorer in extremely and very preterm boys but not girls compared with their full-term peers. (December 2020) - Tulviste, Tiia; Toome, Liis; Männamaa, Mairi; Varendi, Heili
Abstract: Purpose: To date, there are contradictory findings concerning if, at which age, and to what extent children's language development is affected by prematurity at birth. The objective was to compare language skills of extremely preterm (EPT) and very preterm (VPT) girls and boys at 24 months corrected for gestational age (GA) at birth with those of full-term (FT) girls and boys, and to explore the effect of perinatal and demographic factors. Method: Parents of 138 preterm (PT) children born <32 weeks' gestation (48 EPT with GA below 28 weeks, 90 VPT with GA 28–31 weeks) and of 150 FT controls completed the short Estonian version of the MacArthur-Bates Communicative Development Inventory: Words and Sentences (ECDI-II SF). Language skills of PT children were also assessed with the Bayley-III Language Scale (BSID-III), and compared with data from 152 FT controls. Results: Mean scores of all language measurements were significantly lower in boys (not girls) from both PT groups compared to FT girls and boys, while no significant differences were found between PT groups. Across groups, girls obtained significantly better language scores than boys. In PT children, being a girl, and attending day care at corrected age (CA) 2;0 years, predicted a larger expressive vocabulary (measured by the ECDI-II SF). Bayley language composite scores (sum of expressive and receptive language) were higher in PT girls than in boys, and the scores were negatively affected by the number of severe neonatal morbidities. Conclusions: The findings highlight the importance of systematic language-focused assessments (using parents and trained examiners) of EPT and VPT boys, as well as the need to support their development. Highlights: Very preterm boys had poorer language skills than full-term boys and girls at CA 2;0. Language scores did not differ between extremely and very preterm children. Female sex and attending day care predicted a larger expressive vocabulary. Male sex and neonatal morbidities negatively affected Bayley language scores.